The Joker war saga - Tynion, James IV 1987-; Castellucci, Cecil 1969-; Tomasi, Peter (DC Comics, 2021)
"The summer 2020 blockbuster 'The Joker War' is collected in this new hardcover that includes the tie-in chapters starring Batgirl, Red Hood, Nightwing, Catwoman, and, of course, Harley Quinn. As the Clown Prince of Crime battles the Dark Knight Detective head-to-head one last time. The Joker has never wanted to win before--he's never wanted his battle with Batman to end. But now his motivation has shifted. This collection features the Joker's confrontation with Batgirl; his manipulation of the amnesiac Nightwing; and a turf war between Gotham City's many evildoers. Plus, the debut of Clownhunter, a cameo by Ghost-Maker, and an epic battle between Harley Quinn and Punchine."--
"Batman created by Bob Kane with Bill Finger - Nightwing created by Marv Wolfman and George Pérez - Harley Quinn created by Paul Dini and Bruce Timm.
"Originally published in single magazine form in Batman 95-100, Batgirl 47, Detective Comics 1025, Harley Quinn 75, Red Hood and the Outlaws 48, Nightwing 74, Catwoman 25, Batman: The Joker War Zone 1"--Indicia
Keywords: Joker -- Fiktive Gestalt; Batman -- Fiktive Gestalt; Comic